Boreal bog plant communities along a water table gradient differ in their standing biomass but not their biomass production. (25th February 2018) - Korrensalo, Aino; Kettunen, Laura; Laiho, Raija; Alekseychik, Pavel; Vesala, Timo; Mammarella, Ivan; Tuittila, Eeva‐Stiina
Abstract: Question: Peatlands are globally important for carbon storage due to the imbalance between plant biomass production and decomposition. Distribution of both live standing biomass (BM, dry mass g/m 2 ) and biomass production (BMP, dry mass g m −2 growing season −1 ) are known to be dependent on the water table (WT). However, the relations of BM and BMP to WT variation are poorly known. Here we investigated, how the above‐ and below‐ground BM and BMP of three different plant functional types (PFTs), dwarf shrubs, sedges and Sphagnum mosses, relate to natural WT variation within an ombrotrophic boreal bog. In addition, we estimated ecosystem‐level BMP and compared that with ecosystem net primary production (NPP) derived from eddy covariance (EC) measurements. Location: Siikaneva bog, Ruovesi, Finland. Methods: We quantified above‐ and below‐ground BM and BMP of PFTs along the WT gradient, divided into six plant community types. Plant community scale BM and BMP were up‐scaled to the ecosystem level. NPP was derived from EC measurements using a literature‐based ratio of heterotrophic respiration to total ecosystem respiration. Results: BM varied from 211 to 979 g/m 2 among the plant community types, decreasing gradually from dry to wet community types. In contrast, BMP was similar between plant community types (162–216 g/m 2 ), except on nearly vegetation‐free bare peat surfaces where it was low (38 g/m 2 ). Vascular plant BM turnover rate (BMP:BM, per year) varied from 0.14 to 0.30 among the plant community types, being highest in sedge‐dominated hollows. On average 56% of the vascular BM was produced below ground. Mosses, when present, produced on average 31% of the total BM, ranging from 16% to 53% depending on community type. EC‐derived NPP was higher than measured BMP due to underestimation of certain components. Conclusions: We found that the diversity of PFTs decreases the spatial variability in productivity of a boreal bog ecosystem. The observed even distribution of BMP resulted from different WT optima and BMP:BM of dwarf shrubs, sedges and Sphagnum species. These differences in biomass turnover rate and species responses to environmental conditions may provide a resilience mechanism for bog ecosystems in changing conditions. Abstract : The diversity of plant functional types decreased the spatial variability in productivity of a boreal bog ecosystem. The even biomass production across water table gradient resulted from different biomass turnover rates and water table optima of dwarf‐shrubs, sedges and Sphagnum species. The possible consequences of the observed pattern for the resiliency of bog ecosystems in changing conditions are discussed.